A Union Operation of Non-Dominated K-Coterie in Distributed System - NURHIDAYAH NURHIDAYAH; Armin Lawi; Amir Kamal Amir (Department of Mathematics, Hasanuddin University, 2020)
Coterie is a set of quorums which has non-empty intersections and are not part of other quorum. The natural development of the coterie system is k-coterie. The k-coterie consists of 2 types, that are non-dominated k-coterie and dominated k-coterie. The non-dominated k-coterie is more resilient to failure than the dominated k-coterie. Combining two non-dominated k-coterie by applying union operation can result the dominated k-coterie. This study aims to define a combination of the non-dominated k-coterie with non-dominated k-coterie using the expanded union operation. The merger of non-dominated k-coterie with the non-dominated k-coterie produces a non-dominated k-coterie.